CMET-11. RESPONSE TO STEREOTACTIC RADIOSURGERY FOR MULTIPLE BRAIN METASTASES BASED ON HISTOLOGY-SPECIFIC SUBTYPE STATUS. (11th November 2019) - Rooney, Michael K; Chandler, James; Kalapurakal, John; Stupp, Roger; Lesniak, Maciej S; Sonabend, Adam; Kumthekar, Priya; Tate, Matthew; Kruser, Timothy; Lukas, Rimas; Dixit, Karan; Sachdev, Sean
Abstract: BACKGROUND: This retrospective study evaluated the relationship between histologic subtype and treatment outcomes following SRS for the treatment of multiple brain metastases (MBM). METHODS: We analyzed patients with MBM, defined here as >= 3 lesions, treated with SRS at our institution. Primary histologies examined were NSCLC, breast, and melanoma. Patients were categorized according to histology-specific subtypes (NSCLC-EGFR, ALK, KRAS, PD-L1%; breast-HER2, ER, PR; melanoma-BRAF). The primary outcome was local control (defined by RANO-BM) and secondary outcomes included intracranial progression-free survival (iPFS) and overall survival (OS). RESULTS: 141 patients met inclusion criteria (66 NSCLC, 61 breast, and 14 melanoma). HER2+ and BRAF V600E+ lesions had increased rates of local control following SRS (P=0.0048 and P=0.0256, respectively) compared to other breast/melanoma subtypes. EGFR mutation was not associated with increased local control with SRS (71 vs 74%), but increased iPFS (P=0.0031). On multivariable analysis, EGFR+ was independently associated with a decreased time-dependent risk of death (P=0.011). The use of progressively newer generations of EGFR-directed therapies was associated with stepwise decreasing risk of intracranial progression and death. HER2+ disease had improved iPFS and OS (P=0.0058 and P< 0.0001, respectively; it was not an independent risk factor for progression or death; however, the use of HER2-directed antibodies was associated with decreased risk of death (p=0.036). The use of tyrosine kinase inhibitors (i.e. lapatanib) was not associated with improvements, although this was a small subset. CONCLUSIONS: Some histologic subtypes appear to have better control with SRS, with HER2+ breast cancer and BRAF V600E+ melanoma associated with improved outcomes – this requires further validation; a volumetric analysis is pending. This the protective effect of EGFR mutation appears to be partly related to use of EGFR inhibitors, with the use of newer-generation therapies leading to improved outcomes; although local control with SRS remains excellent regardless of the mutation.